Matt Buckner’s Identity Seeking in Green Street Hooligans Movie (2005): A Semiotic Analysis - Rivaldi Alvien Riza; Syahara Dina Amalia (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2022)
This research was conducted to analyze how the identity seeking of the main character, Matt Buckner, in Green Street Hooligans (2005) movie was portrayed semiotically. The term identity can be defined as an expression of the inner self, and the role of ourselves in the world to find the meaning of life and as a guide in life to find happiness. The subject of this research was the Green Street Hooligans (2005) movie directed by Lexi Alexander and the object was the representation of the main character’s identity seeking through images of the scene and dialogues found in the movie. The data were collected through watching and analyzing the movie, reading several related articles, taking notes on the important elements, and classifying the data. In analyzing the data, the researchers used a descriptive qualitative approach and adopted the semiotic analysis technique by Charles Sander Peirce (Hoed, 2007). As A Result, the researchers discovered that Matt Buckner's life before being a Hooligan was just like a normal student’s. Second, Matt Buckner’s identity started to transform when he met Pete and join the GSE firm. The last, and the reasons why Matt Buckner joined the Hooligan was that he felt more appreciated and well-known when he became Hooligan, also he was proud to be a Yankee surrounded by the GSE members. Every sign represented in movie have its meaning, and to comprehend those all signs used a semiotic approach. Based on the result of this research, the researchers able to understand the meaning that represented in the Green Street Hooligans movie.